2008
DOI: 10.1029/2008ja013417
|View full text |Cite
|
Sign up to set email alerts
|

Northeastward motion of nighttime medium‐scale traveling ionospheric disturbances at middle latitudes observed by an airglow imager

Abstract: Nighttime medium‐scale traveling ionospheric disturbances (MSTIDs) observed in 630‐nm airglow images at middle latitudes are known to have a predominantly northwest‐southeast phase surface and to move southwestward in the Northern Hemisphere of Earth. However, the mechanisms of MSTID generation and their systematic southwestward motion have not been clarified. In this paper, we report the “northeastward” motion of the MSTIDs observed at Paratunka, Far East Russia (52.97°N, 158.25°E), using an all‐sky 630‐nm ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 20 publications
(27 reference statements)
7
32
2
Order By: Relevance
“…Meanwhile, we note that the propagation direction of nighttime MSTIDs detected with the Hokkaido radar is not always southwestward. In some cases the propagation direction changes from southwestward to northeastward before midnight: see an example reported by Shiokawa et al [2008], who have pointed out some role of F layer altitude decrease or poleward thermospheric wind in changing the direction.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Meanwhile, we note that the propagation direction of nighttime MSTIDs detected with the Hokkaido radar is not always southwestward. In some cases the propagation direction changes from southwestward to northeastward before midnight: see an example reported by Shiokawa et al [2008], who have pointed out some role of F layer altitude decrease or poleward thermospheric wind in changing the direction.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…It should be noted that the lower‐latitude portions of the images are masked by obstacles. Figure 2b shows the same images as those in Figure 2a, the only difference being that the airglow intensity represented in percentage deviations from 1‐h running averages [e.g., Shiokawa et al , 2008]. The MSTID structures in Figure 2b can be recognized with better clarity than those in Figure 2a.…”
Section: Observationsmentioning
confidence: 94%
“…The all‐sky imager at Paratunka began the automatic airglow imaging observations in August 2007 as part of the Optical Mesosphere Thermosphere Imagers (OMTIs) [ Shiokawa et al , 2008, 2009]. The all‐sky imager has a fish‐eye lens with a 180° FOV and is equipped with a cooled CCD camera with 512 × 512 pixels (operated with 2 × 2 binning, i.e., 256 × 256 pixels).…”
Section: Observationsmentioning
confidence: 99%
“…The results found by Shiokawa et al [2008] and Helmboldt et al [2012] discussed in section 1 provide motivation to explore how the direction of propagation of these MSTIDs depends on the change in F ‐region height. This was done by first estimating the h′F temporal gradient, ∂h′F/∂t, for each VLSS summer nighttime observation.…”
Section: Fluctuation Spectra Sporadic‐e and F‐region Compressionmentioning
confidence: 95%
“…The Cosgrove [2007] simulations also showed that the strength of the coupling was reduced when a significant amount of structure was present within the E s layer. Recent studies based on observations of disturbances over Japan [ Shiokawa et al , 2008] and the southwestern United States [ Helmboldt et al , 2012] have also shown that summer nighttime MSTIDs can propagate toward the northeast, sometimes reversing direction from previously being directed southwestward. These northeastward‐directed waves have been tentatively linked to significant drops in F ‐region height, which may provide a clue to the mechanisms that determine the direction of motion of nighttime, midlatitude MSTIDs.…”
Section: Introductionmentioning
confidence: 99%